Phonetics in Rajeshwori Poetic Poetry - Koirala, Prabha Marahatta (Saptagandaki Journal, 2017)
This article is in Nepali. See the PDF for Nepali Abstract. No English abstract. The Saptagandaki Journal Vol.8 2017: 93-100